Natural Resource Scarcity: A Statistical Analysis - Smith, V. Kerry (The Review of Economics and Statistics, 1979)
Statistical analysis is used to evaluate trends in the relative prices of natural resource commodity aggregates and to predict the adequacy of natural resource supplies. The model incorporates the Brown-Durbin custom test and Quandt's log-liklihood ratio. The results indicate that a relative price series is not stable enough to predict a consistent pattern of change and it would be unwise to base materials and extraction policies on this framework. This conclusion is reached, in part, because of the significant changes in the US economy and institutions in recent years. 22 references.